Judging Performance, Performing Judgments: Race and Performance in Weimar Germany - Fay, Brendan (Current Musicology, 2013)
In the summer of 1930, the pianist John Flaffith concertized throughout Europe and astounded audiences with his vivid interpretations of a varied repertoire, ranging from Debussy and Stravinsky to Bach and Mozart. In Poland, the Kurjer Polski raved: “Yesterday John Flaffith played before a wild audience. What this great artist understands and brings [to the music] can only be appreciated still more by the expert.